THE MODERATING ROLE OF SOCIAL MEDIA MARKETING IN THE RELATIONSHIP BETWEEN KOREAN CELEBRITY ENDORSEMENT AND PURCHASE INTENTION OF KOREAN PRODUCTS IN INDONESIA - Sudhana, Pranakusuma; Iskandar, Donant Alananto (Ultima Management : Jurnal Ilmu Manajemen, 2024)
Abstract- This study aims to examine the moderating role of social media marketing in the relationship between Korean celebrity endorsement and purchase intention of Korean products in Indonesia. A moderation model was developed and was tested using the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique involving 67 respondents. The results revealed that Korean celebrity endorsement positively affects the purchase intention of Korean products in Indonesia. It was also anticipated that social media marketing moderates such relationship. The contribution of this study is that social media marketing was confirmed as a moderator in investigating the consumer behavior. In addition, this study recommended some strategic efforts for Korean businesses in engaging the celebrities to market their products in Indonesia. This paper includes generalizability as its limitation with suggestions to undertake the broader scope of studies. Keywords: Celebrity Endorsement; Purchase Intention; Social Media Marketing; Korean Products